In vivo HSC transduction in humanized mice mediated by novel capsid-modified HDAd vectors - Aphrodite Georgakopoulou; Hongjie Wang; Jiho Kim; Chang Li; André Lieber (Molecular Therapy: Methods & Clinical Development)
We developed an in vivo hematopoietic stem cell (HSC) gene therapy approach consisting of HSC mobilization and intravenous injection of helper dependent adenovirus (HDAd) vectors. While we have demonstrated safety and efficacy of the in vivo approach in CD46-transgenic mice and rhesus macaques, studies in mice with a humanized hematopoietic system could facilitate its potential clinical translation for the treatment of hemoglobinopathies and HIV. Using mild myelo-conditioning in NSGW41 mice and cryopreserved human CD34+ cells from healthy donors we achieved ∼10% human chimerism in peripheral blood. Engrafted primitive human CD45+/CD34+/CD90+-HSCs efficiently mobilized by different approaches involving AMD3100 in combination with granulocyte colony-stimulating factor G-CSF, truncated Groβ (tGroβ), or WU106/tGroβ. At the peak of mobilization, integrating HDAd-GFP vectors were injected intravenously followed by O6BG/BCNU in vivo selection. Long-term stable GFP expression was shown for HDAd5/35 and the new vector platforms HDAd6/3 and HDAd5/35_lam, a fiber/penton-modified vector. Two months post transduction, GFP marking in the periphery were 22.38% (8.17%), 41.12% (10.62%), and 32.15% (4.49%) for HDAd5/35, HDAd6/3, and HDAd5/35_lam, respectively. GFP levels in bone marrow were 33.53% (8.96%), 53.51% (6.95%), and 33.29% (5.21%) and in spleen 32.6% (9.25%), 33.75% (5.47%), and 20.79% (6.15%). Our study describes a new animal model for in vivo HSC transduction with HDAds, with implications for studies with other vectors.